Spontaneous bifacial capping of perovskite film for efficient and mechanically stable flexible solar cell - Junjun Jin; Zhenkun Zhu; Yidong Ming; Yuan Zhou; Jitao Shang; Shaofu Wang; Xiaxia Cui; Tonghui Guo; Dan Zhang; Guanqi Tang; Qianqian Lin; Jinhua Li; et al. (Nature Communications)
Abstract Flexible perovskite solar cells (F-PSCs) are appealing for their flexibility and high power-to-weight ratios. However, the fragile grain boundaries (GBs) in perovskite films can lead to stress and strain cracks under bending conditions, limiting the performance and stability of F-PSCs. Herein, we show that the perovskite film can facilely achieve in situ bifacial capping via introducing 4-(methoxy)benzylamine hydrobromide (MeOBABr) as the precursor additive. The spontaneously formed MeOBABr capping layers flatten the grain boundary grooves (GBGs), enable the release of the mechanical stress at the GBs during bending, rendering enhanced film robustness. They also contribute to the reduction of the residual strain and the passivation of the surface defects of the perovskite film. Besides, the molecular polarity of MeOBABr can result in surface band bending of the perovskite that favors the interfacial charge extraction. The corresponding inverted F-PSCs based on nickel oxide (NiOx)/poly(triaryl amine) (PTAA) hole transport bilayer reach a 23.7% power conversion efficiency (PCE) (22.9% certified) under AM 1.5 G illumination and a 42.46% PCE under 1000 lux indoor light illumination. Meanwhile, a robust bending durability of the device is also achieved.